COMPARISON OF TWO TYPES OF SENSORS AND THEIR EFFECT ON SPRAY QUALITY PEAR TREES - Jawad, Basil R. A.; A.K. Subr, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to reduce the amount of the sprayed solution lost during trees spraying.  At the same time, the concentration of the sprayed solution on the target (tree or bush) must be ensured and to find the best combination of treatments. Two factors controls the spraying process: (i) spraying speed (1.2 km/h, 2.4 km/h, 3.6 km/h), and (ii) the type of sensor. The test results showed a significant loss reduction percentage. It reached (6.05%, 5.39% and 2.05%) at the speed (1.2 km/h, 2.4 km/h, 3.6 km/h), respectively. It was noticed that when the speed becomes higher the loss becomes less accordingly. The interaction between the 3.6 km/h speed and the type of Ultrasonic sensor led to a decrease in the percentage of the spray losses reached to 1.69. For the coverage percentage, the increase in the spraying speed from 1.2 km/h to 2.4 km/h, and then to 3.6 km/h led to a significant decrease in the percentage of coverage (from 17.73% to 13.14%, and then to 11.12%), respectively. The interaction between the type of sensor and the speed has significantly affected the spray density. The speed was 3.6 km/h, and the type of Ultrasonic sensor was superior in obtaining the highest spray density of 83.2 drops/cm2.